(untitled) (Research, Society and Development, 2022)
The Federal Institute of Education, Science and Technology of Rondônia has a Student Assistance Policy (PAE) through which it offers student assistance programs, among which there is the Permanence Assistance Program (PROAP) which grants financial aid to economically vulnerable students to help with transportation and food costs. This work aims to raise the profile of students attended by PROAP in the years 2017, 2018 and 2019. Therefore, a qualitative descriptive research was carried out, considering the aspects of course, shift, gender, age and per capita income. In the end, it was possible to understand that, on average, those covered are from the technical course of Buildings Integrated with High School, morning shift, aged between 18 and 20 years, female, living with 3 people, and with a per capita income of up to half the minimum wage.